[操舟之妙] 钱绪山思想形象的重构 = Between steering and anchoring : reconstructing the philosophical image of Qian De-Hong - 洪耀通 Hoon, Randall Yao Tong (2012)
钱德洪（1496～1574），字洪甫，号绪山，浙江余姚县人，是阳明后学第一代成员中的重要人物之一。他在阳明生前时，与王畿同被视为师门的“教授师”，同样为“天泉证道”的见证人。在阳明死后，绪山更肩负起编辑师门资料的重任；阳明学的重要文集，如《传习录》、《阳明全集》等莫不经其手而成。虽然如此，学界对绪山的研究却极为有限，而或有论者则多以《明儒学案》为绪山所设的“把缆放船”形象为定论，认为他与王畿之“悬崖撒手”乃是绝对而立。本文根据学案文献的细读，发现绪山在良知本体论上认为良知乃是一圆融天成的虚灵本体，而在致知工夫论上则并主先天后天之学。这一方面纠正了今人对绪山“崇后天废先天”的偏激认识，另方面，也说明绪山与王畿之间并无《明儒学案》所言的“精神意境”上的对立。本文再从学术史的角度出发，进一步认为：绪山虽然较多论述后天之学，但是，这是为了针砭时弊、批评先天之学被推向极端后的流弊。其说与时论大异其趣，故时人以后天之学为绪山思想的宗旨。明清交易之际，阳明学面对学界“空谈心性”误国的指控，后人为了维护阳明学，所以强调绪山的后天学问，更将其具体化为“把缆放船”的思想形象。换言之，绪山“把缆放船”的思想形象乃时势使然，其究竟能否反映绪山的整体面貌则值得再议。Qian De-Hong (Qian Dehong, 1496 – 1574) was an eminent scholar among the pioneering members of the Late Yang-Ming School (yangming houxue) , which existed in the late Ming dynasty following their mentor’s – Wang Yang-Ming (Wang Yangming) – death. Qian had extensive contact with Yang-Ming during the latter’s lifetime, and together with a fellow disciple Wang Ji (Wang Ji), both were relied upon as “teaching assistants” by Yang-Ming. Following Yang-Ming’s death, Qian shouldered the responsibility of chronicling Yang-Ming’s teachings, publishing them into texts which shape much of the understanding towards Yang-Ming then and now. Given the important position that Qian occupies in the history of thought concerning the Late Yang-Ming School, it is therefore intriguing that research on his thoughts are limited in this field.